MANAGING CATASTROPHIC RISK: LESSONS FROM CANADA - Kovacs, Paul; Kunreuther, Howard (Assurances)

(untitled) (HEC Montréal, 2001)
Natural disasters are a serious threat to societies around the world. Death, injury and displacement affect hundreds of millions of people each year, while the frequency and severity of property damage is rising at an alarming rate. The UN’s International Decade for Natural Disaster Reduction is a recent effort to promote better management of catastrophic risk; nevertheless, losses remain unacceptably high. The authors believe that the knowledge exists to better manage catastrophic risk, and the Canadian experience demonstrates a new approach to build resiliency and reduce disaster losses.